Hubungan Tingkat Pengetahuan Pasien Terhadap Kejadian Diabetes Mellitus Di Rumah Sakit Universitas Mataram - Muqarrobin, Aoladul (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: to identify relationship between patient knowledge level and the incidence of diabetes mellitus at Mataram University Hospital in 2023. Methods: This article used descriptive analytic with a cross sectional approach. The sampling technique uses accidental sampling. The sample in this study was 70 people using the Chi-Squere statistical test analysis. Results: chi squere test regarding the relationship between the level of patient knowledge and the incidence of diabetes mellitus at Mataram University Hospital in 2023 show that the results of Asymp. Sig. (2-sided) of 0.000. This shows that Asymp. Sig. (2-sided) less than 0.05 (5% error rate), it can be concluded that there is a level of patient knowledge regarding the incidence of diabetes mellitus at Mataram University Hospital. Conclusion: it is necessary to carry out further health promotion in increasing knowledge for Diabetes Mellitus sufferers so that an intervention can be needed to further increase knowledge about the disease, in the management process, medical therapy, the interaction of diet and physical activity and an encouraging environment. clean and healthy living behavior. Thus, patient knowledge about Diabetes Mellitus is a very important means of shaping behavior.